2017
DOI: 10.1021/acsami.7b07857
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost and Green Fabrication of Polymer Electronic Devices by Push-Coating of the Polymer Active Layers

Abstract: Because of both its easy processability and compatibility with roll-to-roll processes, polymer electronics is considered to be the most promising technology for the future generation of low-cost electronic devices such as light-emitting diodes and solar cells. However, the state-of-the-art deposition technique for polymer electronics (spin-coating) generates a high volume of chlorinated solution wastes during the active layer fabrication. Here, we demonstrate that devices with similar or higher performances ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…In fact, even when additional weight was placed on top of the PDMS film to ensure that flat PTB7 : PC 71 BM active layers are produced, the PCE of these push‐coated PSCs only reached values of 2.65 %. We demonstrated that efficient PSCs and OLEDs as well as nanopixel OLEDs can be fabricated by push‐coating with thick PDMS films . In fact, Ikawa et al .…”
Section: Eco‐friendly and Sustainable Active Layer Fabrication Processesmentioning
confidence: 90%
See 3 more Smart Citations
“…In fact, even when additional weight was placed on top of the PDMS film to ensure that flat PTB7 : PC 71 BM active layers are produced, the PCE of these push‐coated PSCs only reached values of 2.65 %. We demonstrated that efficient PSCs and OLEDs as well as nanopixel OLEDs can be fabricated by push‐coating with thick PDMS films . In fact, Ikawa et al .…”
Section: Eco‐friendly and Sustainable Active Layer Fabrication Processesmentioning
confidence: 90%
“…Despite the fact that slot‐die coating and blade‐coating have similar film formation kinetics, PSCs fabricated by blade‐coating generally exhibit higher performances compared to slot‐die coated ones . Recently, unconventional techniques such as electrospray deposition and push‐coating have demonstrated their potential for high performance device fabrication . Here, I will compare the methods that yield relatively high PCEs, namely, spin‐coating, blade‐coating, electrospray deposition and push‐coating, in terms of cost reduction, environment‐friendliness and sustainability (Figure ).…”
Section: Eco‐friendly and Sustainable Active Layer Fabrication Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In as-spun films of F8BT or MEH-PPV, the degree of order achieved is insufficient to assess a real detectable effect by XRD ( Figure 5) [15][16][17]. As previously demonstrated, a higher degree of order may be obtained by annealing these films at high temperature [17].…”
Section: Ordering Of Conjugated Polymer Films By Epitaxialmentioning
confidence: 92%